2013
DOI: 10.1038/jcbfm.2013.66
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vasomotor Reactivity during Hypo- and Hypercapnia in Sedentary Elderly and Masters Athletes

Abstract: Physical activity may influence cerebrovascular function. The objective of this study was to determine the impact of life-long aerobic exercise training on cerebral vasomotor reactivity (CVMR) to changes in end-tidal CO2 (EtCO2) in older adults. Eleven sedentary young (SY, 27 ± 5 years), 10 sedentary elderly (SE, 72 ± 4 years), and 11 Masters athletes (MA, 72 ± 6 years) underwent the measurements of cerebral blood flow velocity (CBFV), arterial blood pressure, and EtCO2 during hypocapnic hyperventilation and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 42 publications
(86 reference statements)
5
90
3
Order By: Relevance
“…Consistent with previous research, this study found that the potential beneficial effects of regular physical activity participation and a healthy body weight on the vascular and cognitive health of young adults have been previously highlighted (Zhu et al, 2014;Zhu et al, 2013). Evidence suggests that physical inactivity, pooper cardiorespiratory fitness, or obesity increases CRP levels and impairs cognitive dysfunction.…”
Section: Crp and Health Indicessupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with previous research, this study found that the potential beneficial effects of regular physical activity participation and a healthy body weight on the vascular and cognitive health of young adults have been previously highlighted (Zhu et al, 2014;Zhu et al, 2013). Evidence suggests that physical inactivity, pooper cardiorespiratory fitness, or obesity increases CRP levels and impairs cognitive dysfunction.…”
Section: Crp and Health Indicessupporting
confidence: 79%
“…Although the data from the adjusted regression analysis highlight the potential pathways of health indices on CRP and cognitive function, our findings do not establish a causal relationship. Therefore, having higher cardiorespiratory fitness level and lower BMI may result in lowered CRP level, thus mediating cognitive function (Ge et al, 2013;Zhu et al, 2013).…”
Section: Crp and Health Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…End‐tidal CO 2 (EtCO 2 ) was measured continuously using a capnograph (Smith Medical, Model 9004). These conditions (5% CO 2 for no longer than one minute at a time) did not result in significant changes in mean arterial blood pressure, heart rate, or oxygen saturation 37. The sequence's parameters were TR/TE = 2000/25 msec, flip angle=80°, field of view=220 × 220 mm 2 , matrix= 64 × 64, 36 slices, thickness=3.6 mm, no gap between slices, 210 volumes.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Aging reduces absolute CBFV, as measured at the middle cerebral artery (MCA) with transcranial Doppler ultrasound. [4][5][6] However, the evidence regarding the effect of age on CVR remains unclear with some studies reporting a decreased CVR, 4,[7][8][9] while others reported no difference. 6,[10][11][12] Different vasodilatory stimuli, ranging from 5 to 7% CO 2 in room air 4,[6][7][8][9][10][11][12] or 5% CO 2 in 95% oxygen, 7 or measures of CBFV versus CBF (transcranial Doppler ultrasound, 4,[6][7][8]10,11 positron emission tomography, 12 xenon inhalation 9 ) represent potential sources of variation amongst studies.…”
Section: Introductionmentioning
confidence: 99%